Development of Think & Go Road Safety Mobile Game using Gamification Approach - Hong, Liang Ni; Ahmad Shaubari, Ezak Fadzrin (Applied Information Technology And Computer Science, 2021)
Road safety is considered as one of the most important topics for children’s education at present due to the increased number of road incidents involving them every year. Think & Go is a road safety mobile game that is designed and developed in English language by using a 3D gamification approach on the Android platform for the target users aged 7 to 12 years old. Game Development Life Cycle (GDLC) model is adopted as the methodology model for the development process. On average, the proposed game received 77.8% of positive feedback for learning outcome acquisition, 73.33% for functionality of the game and 77.77% for user acceptance level of this game from the user testing. This can be concluded that the game provided positive learning outcome, functioning well, suitable for the target user to play and the game also will be monitored to improve in the future.